Molecular methods for the detection of TEM- and SHV-related beta lactamase genes in members of the Enterobacteriaceae - Whitelaw, Andrew Christopher (Division of Medical Microbiology, 2017)
Bacterial resistance to antibiotics is a common and important clinical problem. Beta lactam resistance in Gram negative bacilli is mediated predominantly by beta lactamases, enzymes able to hydrolyse the beta lactam ring. The commonest plasmid mediated beta lactamases in the Enterobacteriaceae are those related to either TEM-1 or SHY-1. Although TEM-1, TEM-2 and SHY-1 do not have activity against extended spectrum beta lactams, their derivatives (TEM-3 and SHY-2 onwards) are able to confer resistance to one or more of these antibiotics. A problem encountered in clinical microbiology laboratories is the lack of a reliable method for the detection of ESBLs, along with the lack of a quick, reliable method of differentiating TEM-related genes from SHY -related genes. The primary aim of this study was to evaluate two molecular techniques for the detection of SHY and TEM-related genes in clinical isolates. The study sample consisted of 209 clinical isolates of enteric Gram negative bacilli, isolated at Groote Schuur Hospital microbiology laboratory. The isolates had all been selected on the basis of resistance to one or more of the extended spectrum beta lactams. These isolates were all identified, and the susceptibility of each to a variety of beta lactam antibiotics determined. Using this information, 45 isolates, belonging to different genera and with differing antimicrobial sensitivity patterns, were selected for this pilot study. These 45 isolates consisted of 24 Klebsiella spp., 14 Enterobacter spp., 3 Citrobacter spp., 2 Salmonella spp., 1 Pantoea agglomerans and 1 Serratia marcescens.